Stormwater evaluation and site assessment - a multidisciplinary approach for stormwater Best Management Practices (BMPs) - Padmanabhan, Aarthi (Kansas State University, 2009)
Stormwater management is typically approached from different perspectives by practicing professionals. As such, stormwater planning/design is not always completed as a multi-disciplinary coalition of experts using holistic and synergistic methods. For a number of years, engineers and design professionals, particularly landscape architects, have been employing various strategies and techniques to address on-site stormwater management in terms of water quality and quantity. There is increasing awareness that in order to create solutions that are effective over both the short and long-term a landscape architect’s approach needs to account for the health, safety and welfare perspectives carried by engineers, the unique aspects of particular project sites, their surroundings and bio-regional context, as well as the perceptions of clients, other key stakeholders, and the broader public. This research investigates the various criteria integral to developing an analytic framework for ecologically-appropriate stormwater planning/design (Sustainable Stormwater Evaluation and Site Assessment or SSWESA). SSWESA is proposed as a type of decision-tree for site analysis of sustainable systems pertaining to stormwater. Using the SSWESA process is expected to help researchers and professionals make better planning and design decisions as they select and implement appropriate best management practices (BMPs) for a given site and context. My intent in developing SSWESA is to help designers assess existing and potential stormwater functions at the site scale in order to promote sustainable planning and design based upon the important principle: “First, do no harm”. It is also my intent to promote further research related to sustainability by providing references and sources from experts in the various fields related to ecologically-based stormwater management. A review of the literature related to ecological factors relevant to low impact stormwater management assisted in the development and refinement of the criteria for stormwater assessment and evaluation. In this report, the SSWESA framework is tested on a public school property in Manhattan, Kansas to demonstrate how the framework is applied and to understand the questions and issues that arise from its use.
Keywords: Stormwater management; Best management practices (BMPs); Landscape architecture; Artful rainwater design (ARD); Water quantity and stormwater runoff; Water quality and Nonpoint source pollution (NPS); Landscape Architecture (0390)